2021
DOI: 10.33448/rsd-v10i3.13686
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance, thermal and blood parameters of Japanese laying quails at different cage stocking densities

Abstract: This study aimed to evaluate the effects of different stocking densities on the performance, eggshell quality, surface body temperature and hematological parameters of Japanese laying quails based on physiological indicators of animal welfare. Two hundred and thirty seven-week-old Japanese quails were used in this experiment. The quails were completely randomized to four stocking densities: 112.2 (T1), 102 (T2), 93.5 (T3), and 86.31 (T4) cm²/quail and five replicates each. Hematological parameters were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
1
3
0
3
Order By: Relevance
“…In a later study, El-Tarabany (2016) found that laying quails kept at 200 cm 2 /bird exhibited significantly better means of interior traits of egg quality than those of quails kept at higher cage SD (167 or 143 cm 2 /bird). Our results, however, are in line with those reported by Bourdon et al (2021) they evaluated the effects of four cage SD (112.2, 102.0, 93.5 and 86.3 cm 2 /bird) on egg quality parameters of laying Japanese quails and found that eggshell quality criteria were not affected by different cage SD applied. However, Ratriyanto et al (2020) found significant reduction in ST with increasing cage SD from 40 to 50 quails/ m 2 .…”
Section: Egg Quality Of Japanese Quailsupporting
confidence: 93%
See 2 more Smart Citations
“…In a later study, El-Tarabany (2016) found that laying quails kept at 200 cm 2 /bird exhibited significantly better means of interior traits of egg quality than those of quails kept at higher cage SD (167 or 143 cm 2 /bird). Our results, however, are in line with those reported by Bourdon et al (2021) they evaluated the effects of four cage SD (112.2, 102.0, 93.5 and 86.3 cm 2 /bird) on egg quality parameters of laying Japanese quails and found that eggshell quality criteria were not affected by different cage SD applied. However, Ratriyanto et al (2020) found significant reduction in ST with increasing cage SD from 40 to 50 quails/ m 2 .…”
Section: Egg Quality Of Japanese Quailsupporting
confidence: 93%
“…El-Tarabany et al (2015) reported that increasing the SD for Japanese quails from 200 to 143 cm 2 per bird depressed their exterior and interior parameters of egg quality. However, Bourdon et al (2021) observed that productive performance and eggshell quality traits of laying quails were not affected by different stocking densities in cages (112.2, 102.0, 93.5 and 86.3 cm 2 /bird).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…At present, the cage system is the most commonly used housing system for quail, as it facilitates overall management, reduces labor costs, and allows for increased breeding and production density per area. The use of quail housing density has been studied for reducing egg production costs and maximizing the occupancy of sheds (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A bateria de gaiolas é o sistema de alojamento mais utilizado para codornas atualmente por facilitar os manejos de uma forma geral, reduzir custos com mão-de-obra e permitir maior densidade de criação e produção por área. A densidade de alojamento de codornas tem sido estudada visando a redução dos custos de produção de ovos e a maximização de ocupação do galpão (10,11) .…”
Section: Introductionunclassified